A rapid method for the determination of toxic dye using FTIR spectroscopy - Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed; Qudsieh, Sam Yassin (2008)
A simple, new and rapid method was developed to determine toxic dyes content in textile and other products using Fourier transform infrared (FTIR) spectroscopy with Attenuated total reflectance (ATR) element and KBr transmission cell. The wavelengths used were selected using pure dyes and dye mixtures. Transmittance values from the wavelengths regions 3500–2650 and 1400–800 cm-1 and partial least square (PLS) regression method were used to derive FTIR spectroscopic calibration model for dyes containing –N=N– in their structure. The coefficient of determinations (R2) for the models were computed by comparing the results obtained from FTIR spectroscopy against the actual values of the dyes concentrations. R2 were 0.9321 and 0.9819 for two samples of toxic dyes respectively. The standard errors (SE) of calibrations were 1.84 and 1.36 respectively. The calibration model were cross validated within the same set of samples and the standard deviation (SD) of the difference for repeatability and accuracy of the FTIR method were determined. With its speed and ease of data manipulation, FTIR spectroscopy is a useful alternative method to wet chemical methods for rapid and routine detection of toxic dyes in such products for quality control.